HUMAN RESOURCE PERFORMANCE IMPROVEMENT INTRINSIC MOTIVATION BASED MODEL AND SKILL VARIATION IN TERMS OF INFORMATION COMMUNICATION TECHNOLOGY - Dwi Priyo Adianto; Widodo Widodo (UNISSULA, 2017)
This study aims to test a research model in which the performance of human resources is related to intrinsic motivation, skill variation and information com- munication tecnology. There are as many as 83 respondents who fill out and complete questionnaires about human resource performance, skills variation, intrinsic motivation and information comunication tecnology. Data collection methods by census. The higher the skill variation, the higher the skill variation, the higher the human resource performance, the higher intrinsic motivation, the higher the performance of the human resources performanceKeywords : Human Resource Performance, Skill Variation, Intrinsic Motivation, Employee Performance